2003
DOI: 10.1038/sj.gene.6363912
|View full text |Cite
|
Sign up to set email alerts
|

Variation in immune response genes and chronic Q fever. Concepts: preliminary test with post-Q fever fatigue syndrome

Abstract: Acute primary Q fever is followed by various chronic sequelae. These include subacute Q fever endocarditis, granulomatous reactions in various organs or a prolonged debilitating post-infection fatigue syndrome (QFS). The causative organism, Coxiella burnetii, persists after an initial infection. The differing chronic outcomes may reflect variations within cytokine and accessory immune control genes which affect regulation of the level of persistence. As a preliminary test of the concept we have genotyped QFS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Our results do not discount a protective role for Nramp1 during animal infection. Indeed, patients with post-Q fever fatigue syndrome show an increased frequency of allelic variants of Nramp1 [63]. Conversely, there is no correlation between the expression of Nramp1 and the sensitivity of various inbred mouse strains to C .…”
Section: Discussionmentioning
confidence: 99%
“…Our results do not discount a protective role for Nramp1 during animal infection. Indeed, patients with post-Q fever fatigue syndrome show an increased frequency of allelic variants of Nramp1 [63]. Conversely, there is no correlation between the expression of Nramp1 and the sensitivity of various inbred mouse strains to C .…”
Section: Discussionmentioning
confidence: 99%
“…Although predisposing host factors are clearly important in the development of human acute or chronic Q fever (32,51), C. burnetii isolates also exhibit distinct phenotypes in terms of infectivity of cell culture (53), cytopathic effects on host cells (53,66), and pathogenicity in animal models of Q fever (43,64,68). The general consensus of these studies is that the NMI reference isolate (genomic group I), biologically representative of human acute disease isolates, is more infectious, grows faster in cell culture, and is more virulent in animal models of infection than chronic disease isolates of genomic groups IV and V. Evidence of C. burnetii pathotype-specific ORFs was recently provided by Glazunova et al (24), who found by multispacer sequence typing analysis that both plasmid type and genotype correlate with disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the immune reaction in naturally or experimentally infected individuals have suggested that cellular immunity and the synthesis of IFN γ are essential for control of Coxiella burnetii infection [6870]. Helbig et al [69] demonstrated the predominant role of IFN γ , its level of production determining the outcome of infection. Indeed, IFN γ has been successfully tested to treat Q fever in patients not responding to antibiotic treatment [71, 72].…”
Section: Pathogenesismentioning
confidence: 99%